Gambaran tingkat pengetahuan swamedikasi obat diare pada warga Desa Hidirasa Kecamatan Wera Kabupaten Bima - Hesti Wulandari; Ni Made Amelia Ratnata Dewi; Raisya Hasina (Universitas Mataram, 2023)
Diarrhea is a health problem with high morbidity and mortality rates. Mild diarrhea is a disease that can be treated with self-medication out by the people of Hidirasa Village because of the limitations of health service centers and places to buy medicines which are still lacking and quite far away. The limited knowledge of the community is one of the sources of errors in treatment. This research was conducted with the aim of knowing the level of knowledge of self-medication of diarrhea medicine in the residents of Hidirasa Village, Wera District, Bima Regency. This research is a descriptive observational study using a cross sectional research design with a cluster sampling technique of 100 respondents. Data was obtained by distributing questionnaires to respondents. The instrument used was tested for validity and reliability. From the 25 statement items, it was declared valid because the r-count value was >0.3 and the reliability test results obtained the Cronbach's Alpha value of 0.888. In the analysis of the level of knowledge of the community is done using Microsoft Excel and categorized into good, sufficient, and less. Based on the results of the study, it can be concluded that the level of knowledge of self-medication of diarrhea drugs in the Hidirasa village community is in the good category of 36%, 62% have sufficient knowledge, and 2% have less knowledge.